Egg Storage and Incubation Temperatures Alter Parthenogenetic Development in Chinese Painted Quail Eggs - Rosa, P. Santa; Parker, H.M.; Kiess, A.S.; McDaniel , C.D. (International Journal of Poultry Science, 2015)
Parthenogenesis, embryos from unfertilized eggs, often exhibit delayed development at oviposition and throughout incubation at standard incubational temperature. Additionally, the first egg in a clutch sequence is more likely to exhibit parthenogenesis than subsequent eggs. Because the first egg in a clutch sequence stays in the hen’s body longer, it is possible that the temperature of the hen’s body accelerates parthenogenetic development. Increasing storage and incubational temperature may simulate the hen’s body temperature and increase the incidence of parthenogenesis. Therefore, the objective of this study was to determine if storage and incubational temperatures impact parthenogenetic development in virgin Chinese Painted quail. Daily eggs were collected, labeled and divided among 3 different storage temperatures (20, 30 or 40°C). Eggs were incubated at 37°C for 10 d or 42°C for 48 h then returned to the standard incubational temperature of 37°C for the remaining 8 d of incubation. After 10 d of incubation, albumen pH and parthenogen size was measured for each egg. At an incubational temperature of 42°C, eggs stored at 20°C yielded the highest percentage of parthenogens. Also, eggs stored at 20°C and incubated at 42°C yielded the lowest albumen pH. As storage temperature increased, parthenogen size increased when eggs were incubated at 37°C. Also when eggs were stored at 30°C, embryo size was larger when incubated at 42°C for 48 h as compared to incubation at 37°C. In conclusion, elevated egg storage or incubational temperatures alter albumen pH, the incidence of parthenogenesis and the size of parthenogenetic embryos.